ANALISIS KOMODITAS UNGGULAN TANAMAN PANGAN PADA LAHAN TERSEDIA DI KABUPATEN BOVEN DIGOEL, PROVINSI PAPUA - Marianus Komanik Keratorop; Widiatmaka Widiatmaka; Suwardi Suwardi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Economic characteristic of The Boven Digoel Regency is dominated by agriculture. Food crops has an important role in agricultural and economic development in Boven Digoel Regency. The objectives of this paper are : (1) Identifying and establishing food crops as the superior commodities, (2) Delineating the land availability for superior food crops development, (3) Arranging direction development of superior food crops commodities in Boven Digoel Regency. The methodology used in this paper were consisted of the analysis of Location Quotient (LQ), Defferential Shift within Shift Share Analysis (SSA), and land availability analysis. Results of LQ and SSA analyzes showed that cassava, sweet potato, paddy, corn and peanuts are the superior food crops commodities. Analyzes of land availability showed thazt there are three  scenarios necessary in determining land availability for food crops. In the first scenario, available land covers an area of 36,227 ha, in the second scenario available land covers an area of 43,401 ha, while in the third scenario, available land covers an area of 610,990 ha.